Anticipatory cortico-cortical interactions: switching the task configuration between effectors. - Serrien, D; Pogosyan, A; Cassidy, M; Brown, P (2004)
Cognitive regulation enables a subject to plan actions according to context and to respond in a flexible manner to environmental conditions. This implies that foreknowledge about a change in system configuration will trigger preparatory activity in anticipation of the impending transformation. In the present study, we evaluate a unimanual task under two performance conditions that affected the cognitive context, and examine modulations in cortico-cortical interactions as determined by EEG coherence. The right hand movement was performed in an experimental paradigm that necessitated in some trials a voluntary and predictable switch towards a left hand movement, whereas in other trials no switch was required and movement of the right hand continued. The data showed that execution of the right hand movement was associated with an increased degree of task-related coherence in the alpha frequency band (8-12 Hz) in the switching as compared to the no switching condition, and this was most apparent for fronto-parietal connections of the movement-driving (left) as well as for the primed (right) hemisphere. For the primed hemisphere, we observed that the information flow was driven from the F4 electrode overlying the prefrontal area, which suggests that anticipatory preplanning occurred. These data indicate that higher-order cognitive operations bias cortico-cortical interactions in respect of an upcoming switch of the task settings between effectors by recruiting neural resources proactively. Dynamic adjustments in the alpha band suggest that low frequency activity is a characteristic of distributed information processing related to movement planning.